Divine Revelation in the Philosophical Essays of al-Fārābī in Comparison with the Mystical Thoughts of Ibn ‘Arabī - Ghorbanali Karimzadeh Gharamaleki; Abdullah HosseiniEskandian; Nur Hidayat Wakhid Udin (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2021)
One of the most important concepts discussed in Islamic sciences is the explanation of divine revelation. Al-Fārābī and Ibn ‘Arabī are among the leading Islamic thinkers who have tried to explain divine revelation according to their style and school of thought. Al-Fārābī considers revelation as receiving knowledge from the active intellect while Ibn ‘Arabī considers it as the revelation of abstract rational meanings from God to the prophets. Examining and comparing their views on divine revelation can acquaint us with their thoughts on how the revelation and its quality came about as well as their intellectual similarities and differences. Employing a descriptive-analytical method, this article examines the essence of revelation in the thought of these two scholars. It also analyzes the quality and degree of revelation in their minds. The discussion ends with a comparison of their views on this issue. Al-Fārābī and Ibn ‘Arabī consider revelation as a divine command revealed by God directly or indirectly to the prophets to guide their people. While al-Fārābī tries to explain the revelation based on the prominent role of the Active Intellect, Ibn ‘Arabī pays attention to the issue of divine grace in sending of the revelation and the imagination of the prophets.